INFLUENCE OF SPRING REPLENISHING FEED RESERVES OF BEE FAMILIES ON THEIR PRODUCTION OF POLLEN, BEE BREAD AND HOMOGENATE OF DRONE LARVAE - Nedashkovsky, V. M.; Razanov, S. F. (Scientific Progress & Innovations, 2020)
Beekeeping is an important branch of agriculture. Bees produce a valuable dietary and medicinal product – honey and raw materials for industry – wax. An important role in the success of beekeeping is played by providing bees with enough feed of good quality. Insufficient supply of bees with carbohydrate feed has an unsatisfactory effect on the development and productivity of bee families, which in its turn negatively affects the profitability of apiaries. Studying the influence of spring replenishment of feed to bee colonies on their production of pollen, bee bread and drone homogenate was carried out. The research was conducted in Tyvriv district of Vinnytsia region on bee families of the Ukrainian breed. The study of the effectiveness of using glucose-fructose syrup in bee feeding was carried out during the period of supporting honey flow in May and the calculation of brood grown by bees was made in accordance with methodical recommendations. The composition of nectar-pollen bearing plants in the central forest-steppe was determined by botanical features of plants, trees and shrubs. The development and productivity were investigated by studying the strength of bee colonies and counting the products obtained at the end of the season. The conditions of keeping and caring after the experimental families during the research were the same. Glucose-fructose syrup is made from high-quality corn starch by its enzymatic hydrolysis to glucose, followed by isomerization of part of glucose into fructose and subsequent purification through carbon columns and ion exchange resins. This syrup has trace elements, B vitamins and all essential amino acids. Scientific studies show that additional feeding bee colonies with glucose-fructose syrup increases the production of bee pollen, bee bread and drone larvae homogenate by 89.7 %, 78.6 % and 23.7 %, respectively, as compared with analogues of the control group.